Gingival crevicular fluid levels of MMP-8, MMP-9, TIMP-2, and MPO decrease after periodontal therapy - Marcaccini, Andrea M.; Meschiari, Cesar A.; Zuardi, Leonardo R.; De Sousa, Tiago Sampaio; Taba Jr, Mario; Teofilo, Juliana M.; Jacob-Ferreira, Anna L.B.; Tanus-Santos, Jose E.; Novaes Jr, Arthur B.; Gerlach, Raquel F. (Journal of clinical periodontology, 2010)
Marcaccini AM, Meschiari CA, Zuardi LR, de Sousa TS, Taba M, Teofilo JM, Jacob‐Ferreira ALB, Tanus‐Santos JE, Novaes AB, Gerlach RF. Gingival crevicular fluid levels of MMP‐8, MMP‐9, TIMP‐2, and MPO decrease after periodontal therapy. J Clin Periodontol 2010; 37: 180–190. doi: 10.1111/j.1600‐051X.2009.01512.x. Background: This study aimed at comparing the levels of matrix metalloproteinase (MMP)‐8, tissue Inhibitor of MMPs (TIMP)‐1 and TIMP‐2, Myeloperoxidase (MPO), and MMP‐9 in the gingival crevicular fluid (GCF) of chronic periodontitis (CP) patients and controls at baseline and 3 months after non‐surgical therapy. Materials and Methods: GCF was collected from one site of 15 control subjects and 27 CP patients. MMP‐8, MMP‐9, TIMP‐1, and TIMP‐2 were determined by Enzyme‐linked immunoabsorbent assay; different forms of MMP‐9, by gelatin zymography; and MPO, colorimetrically. Results: At baseline, higher levels of MMP‐8, TIMP‐2, MPO, and the 87 kDa‐MMP‐9 were found in patients compared with controls (p<0.001), and these molecules decreased after therapy (p<0.03). There were no differences between the groups with respect to the higher molecular forms of MMP‐9 (180, 130, 92 kDa) or total MMP‐9 at baseline. No differences were observed in TIMP‐1 levels. In controls, decreased levels of TIMP‐2 and the higher molecular forms of MMP‐9 (180, 130, 92 kDa) were found 3 months after therapy compared with baseline (p<0.01). Conclusions: Higher levels of MMP‐8, TIMP‐2, MPO, and 87 kDa MMP‐9 were found in the GCF of patients compared with controls, and these markers decreased 3 months after periodontal therapy.